Pengembangan Learning Management System (LMS) dalam Mengelola Kelas pada Mata Pelajaran Kejuruan di SMKN 1 Pandeglang - Kania, Siti Adira; Dayurni, Popi; Ismatullah, Ismatullah (ISLAMIKA, 2025)
This research is motivated by the lack of technology utilization in classroom management. There is a need for new innovations in the creation of classroom management systems. The purpose of this research is to determine the validity and effectiveness of the classroom management system using the Learning Management System (LMS) in managing vocational subjects at SMKN 1 Pandeglang. This research uses the Research and Development (RnD) methodology, with the Rapid Application Development (RAD) model, which includes the stages of Requirement Planning, User Design, Construction, and Cutover. Data collection techniques in this study include observation, distributing questionnaires, and documentation. The data collection instruments used in this study are questionnaires in the form of validity, practicality, and effectiveness instruments. The data analysis technique in this study employs descriptive analysis in the form of results from tests of validity, practicality, and effectiveness. Based on the research results, the validity evaluation by 4 validators received an average score of 86.6%, with a rating of "Very Valid," indicating that the Learning Management System (LMS) is suitable for use as a classroom management system. Additionally, the effectiveness evaluation by 35 students showed an average score of 93.2%, with a rating of "Very Good," indicating that the Learning Management System (LMS) is effective in classroom management.